Synthesis and Characterization of Novel Purpurinimides as Photosensitizers for Photodynamic Therapy - Cui, Bing Cun (Molecular Diversity Preservation International (MDPI), 2014)
A series of novel purpurinimides with long wavelength absorption were designed and synthesized to develop novel and potential photosensitizers. These compounds were investigated through reduction, oxidation, rearrangement reaction and amidation reactions of methyl pheophorbide a. They demonstrated a considerable bathochromic shift of the major absorption band in the red region of the optical spectrum (695–704 nm). Newly synthesized purpurinimides were screened for their antitumor activities, and showed higher photodynamic efficiency against A549 cell lines as compared to purpurin-18 methyl ester. The results revealed the novel purpurinimides could be potential photosensitizers.